2020
DOI: 10.1080/13102818.2020.1827979
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of photosynthetic- and yield-related traits towards grain yield in wheat at the individual quantitative trait locus level

Abstract: Grain yield improvement in wheat (Triticum aestivum L) requires understanding of the genetic control of grain yield components and other related traits. In this study, a total of 82 and 314 quantitative trait loci (QTLs) were associated with grain yield and grain yield components after harvest and photosynthetic traits at the seedling, heading and grain filling stages from a recombinant inbred line population by normal and multivariate QTLs analysis, respectively. Sixty-one QTL clusters explained from 4.42% to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(66 reference statements)
1
1
0
Order By: Relevance
“…Maintaining the photosynthetic rate under low P compared to under adequate P at the later stage could contribute to greater grain yield in RAC875 under low P. This result is consistent with our previous finding where under low P, RAC875 was better in maintaining phosphorylated sugars necessary for the biosynthesis of sugars and starch . This result is similar to previous studies that showed that the grain yield was positively correlated with photosynthetic rate at heading and the grain filling stage in wheat (Yu et al, 2020), and at stages before flowering in sorghum (Peng et al, 1991).…”
Section: Differences In Gas Exchange and Chlorophyllsupporting
confidence: 92%
See 1 more Smart Citation
“…Maintaining the photosynthetic rate under low P compared to under adequate P at the later stage could contribute to greater grain yield in RAC875 under low P. This result is consistent with our previous finding where under low P, RAC875 was better in maintaining phosphorylated sugars necessary for the biosynthesis of sugars and starch . This result is similar to previous studies that showed that the grain yield was positively correlated with photosynthetic rate at heading and the grain filling stage in wheat (Yu et al, 2020), and at stages before flowering in sorghum (Peng et al, 1991).…”
Section: Differences In Gas Exchange and Chlorophyllsupporting
confidence: 92%
“…Gas exchange such as photosynthetic rate can also be used to evaluate the photosynthetic potential of plants (Johnson and Murchie, 2011). For example, a recent study in wheat showed a positive correlation between grain yield and photosynthetic rate at the heading and grain filling stage (Yu et al, 2020). A similar result in wheat grown under well-watered conditions was also reported by Wasaya et al (2021).…”
Section: Introductionmentioning
confidence: 64%